1995
DOI: 10.1007/bf01719944
|View full text |Cite
|
Sign up to set email alerts
|

HBsAg subtype distribution among different populations of HBsAg carriers in Spain

Abstract: Data concerning the HBsAg subtype distribution in Spain are out-of-date and confined to a restricted geographical area. Furthermore, the complex distribution observed in the countries surrounding Spain prevents any prediction. To obtain further data on HBsAg subtype distribution among Spanish HBsAg carriers, subtyping analysis (d and y determinants) was performed in 670 samples from subjects belonging to various epidemiological risk groups and coming from different geographical areas of the country. Similar fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The influence of co‐infection with other viruses on the level of surrogate markers could be important, due to the frequency of this co‐infection in HIV‐positive IVDAs. Our cohorts showed rates of co‐infection with HBV and HCV of 20% and 83%, respectively These figures were similar to those measured in IVDAs in other studies [20–24], although the HBV ratio was higher than expected. The prevalence of HBsAg in IVDAs ranged between 5% and 15% [20,21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The influence of co‐infection with other viruses on the level of surrogate markers could be important, due to the frequency of this co‐infection in HIV‐positive IVDAs. Our cohorts showed rates of co‐infection with HBV and HCV of 20% and 83%, respectively These figures were similar to those measured in IVDAs in other studies [20–24], although the HBV ratio was higher than expected. The prevalence of HBsAg in IVDAs ranged between 5% and 15% [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Our cohorts showed rates of coinfection with HBV and HCV of 20% and 83%>, respectively These figures were similar to those measured in IVDAs in other studies [20-241, although the HBV ratio was higher than expected. The prevalence of HBsAg in IVDAs ranged between 5% and 15% [20,21]. Infections with other viruses such as HTLV-I, HTLV-I1 and HIV-2 are currently very unusual in Spain and were not studied [25-271.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the 13 genotype A strains from patients native from Spain displaying Asn 207 and Leu 209 , these 19 strains represented 8.2 % of the 231 HBV strains from autochthonous carriers in the present study, which demonstrates the emergence of exotic HBV strains in the country. This is already known for the American genotype F strains [Echevarría et al, 1995;Rodríguez-Frías et al, 1995;Sola et al, 2002;Echevarría and León, 2004] and has also been suggested for African strains belonging to genotype E . Our data regarding genotype A strains confirm the spread of HBV strains originating from sub-Saharan Africa in the Spanish population.…”
Section: Discussionmentioning
confidence: 73%
“…Data on characteristics of HBV strains in Spain was derived from reports on HBsAg subtypes [Pedreira et al, 1974[Pedreira et al, , 1975Echevarría et al, 1994Echevarría et al, , 1995 and reports on HBV genotypes [Rodríguez-Frías et al, 1995;Sá nchezTapias et al, 2002;Echevarría and León, 2004]. These studies showed similar prevalence for the subtypes ad and ay, and a dominance of genotypes D and A was noted among the HBV carriers.…”
Section: Discussionmentioning
confidence: 94%
“…The distribution of the two major subtypes of HBsAg (ad and ay) in our environment is approximately 50% for each one, ay being more frequent in drug addicts who use the parenteral route (22). We have demonstrated that the pooling method improves sensitivity, that is, decreases the detection limit of an immunoassay used for the determination of the two major HBsAg subtypes.…”
Section: Is Interpreted To Be Reactive) Efecto De Neutralización Delmentioning
confidence: 94%